Strategi Guru Pendidikan Agama Islam dalam Menanamkan Nilai-nilai Etika Islam pada Siswa : Pedagogical Strategies for Instilling Islamic Ethical Values among Students in Islamic Education - Amdiah; Maria Ulfah; Firdaus (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2025)
This study explores the strategies used by Islamic Religious Education (PAI) teachers to instill Islamic ethical values in students at SMP Al Wathoniyah 9. The research is driven by the growing need to shape strong ethical character in today’s younger generation. It focuses on the various approaches adopted by teachers, such as setting a good example, encouraging positive habits, giving advice, sharing Islamic stories, and applying a system of rewards and punishments. In addition to these personal approaches, the teachers also implement instructional strategies like expository teaching and cooperative learning methods. The study employs a qualitative field research approach, with data gathered through observations, interviews, and documentation conducted at SMP Al Wathoniyah 9. The participants in this research include both PAI teachers and students. The findings reveal that these combined strategies have a significant positive impact. Students show greater openness to guidance, improved manners, and are more easily directed toward behaviors that align with Islamic ethical values. These results highlight the effectiveness of merging personal engagement with interactive teaching methods in supporting students’ character development